Circular supply chain relationships for food redistribution. (15th February 2022) - Sundgren, Caroline
Abstract: The issue of food waste has received increased attention in recent years, from both researchers and practitioners, due to the unethical and negative environmental implications of wasting food. Recovering waste effectively depends on existing or emergent relationships between food waste generators and receivers that facilitate food redistribution. Although previous studies have identified the importance of the relational aspect for achieving circularity, the extant literature has not yet fully explored redistribution in practice. The present study fills this void by exploring the formation of relationships for food redistribution that enhance circularity at the end of the food supply chain through 18 interviews in the food donor–receiver dyad. The results of the study reveal four categories – (1) ongoing redistribution, (2) sporadic redistribution, (3) the establishment of new relationships, and (4) relationship imbalance – that highlight that redistribution is supply-driven and thereby depends on a highly responsive demand side. The results are synthesised into a framework that presents improvements in surplus food recovery. Highlights: Surplus food can be a resource for other actors, and it is crucial to have relationships with actors who can recover the food. Redistribution relationships among food waste generators and receivers of surplus food tend to be distant. Redistribution relationships are driven by availability of supply, as amounts and products types are unknown for receivers. New connections are often created through inter-personal connections.